2021
DOI: 10.1186/s12915-021-00985-7
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and trans-regulation of histone modification in the A and B subgenomes of polyploid wheat during domestication and ploidy transition

Abstract: Background Polyploidy has played a prominent role in the evolution of plants and many other eukaryotic lineages. However, how polyploid genomes adapt to the abrupt presence of two or more sets of chromosomes via genome regulation remains poorly understood. Here, we analyzed genome-wide histone modification and gene expression profiles in relation to domestication and ploidy transition in the A and B subgenomes of polyploid wheat. Results We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Polyploidization induces rapid morphologic changes in wheat [ 45 ]. Changes of genetic sequences and epigenetic marks including DNA methylation and histone modifications are reported to be involved in gene regulation and phenotypic changes during wheat polyploidization [ 40 , 45 , 46 ]. By comparing hexaploid wheat with tetraploid and diploid relatives, we found a positive correlation between chromatin interaction changes and expression changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidization induces rapid morphologic changes in wheat [ 45 ]. Changes of genetic sequences and epigenetic marks including DNA methylation and histone modifications are reported to be involved in gene regulation and phenotypic changes during wheat polyploidization [ 40 , 45 , 46 ]. By comparing hexaploid wheat with tetraploid and diploid relatives, we found a positive correlation between chromatin interaction changes and expression changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Allopolyploidization resulting in divergent genomes in a single cell is believed to trigger “genome shock” and to cause broad gene-expression aberrations, which could be detrimental to newly formed polyploidy ( 5 , 6 ). Continuous efforts have revealed that epigenetic modification changes ( 7 9 ), homologous recombination ( 10 ), three-dimensional chromatin conformation ( 11 , 12 ), transposable element (TE) reactivation ( 13 ), and small interfering RNA expression ( 14 ) are important factors driving gene-expression bias or novelty in plant polyploidization. However, there is still a lack of understanding of the mechanisms controlling gene transcription changes mediated by cis -regulatory elements (CREs) after plant polyploidization.…”
mentioning
confidence: 99%
“…Moreover, T. aestivum gene diversity significantly reduced as a result of subsequent polyploidy events. Its D genome was found to conserved more trait loci than in subgenomes A and B ( Berkman et al, 2011 ); however, it was also found that subgenome D can modify 42.8% of alternative splicing patterns (during gene expression, an alternative splicing process allows a single gene to code for numerous proteins) of subgenomes A and B ( Yu et al, 2020 ), meaning that domestication at the hexaploid level had a greater effect on genetic modifications between subgenomes than same processes at the tetraploid level ( Lv et al, 2021 ). This suggests that subsequent polyploidy events lead to the loss of more genetic information to recruit microorganisms from the bulk soil.…”
Section: Discussionmentioning
confidence: 99%